Knowledge creation influences the awareness attribute of sustainability campus management - Rusli, Nazrul; Mohd. Hussain, Mohd. Ramzi; Nizarudin, Norhanis Diyana (Semarak Ilmu Publishing, 2024)
The abstract explores the relationship between knowledge creation and its impact on the awareness attribute within the context of sustainability campus management. It delves into how knowledge creation shapes and influences the level of awareness associated with sustainable practices in campus management. The concept of sustainability campus management has become increasingly important in today's organizations and institutions. Effective knowledge management is crucial for the success and sustainability of campus management. The creation of knowledge is essential for developing a culture of knowledge awareness. When individuals within an organization or institution know the importance of knowledge, they are more likely to seek out and share information actively. It can lead to a continuous knowledge creation and sharing cycle, which can benefit the entire organization. The study aims to uncover how the generation and dissemination of knowledge contribute to fostering a heightened consciousness of sustainability objectives among stakeholders. Furthermore, knowledge creation is significant for promoting sustainability in campus management. By creating and sharing knowledge about sustainable practices, institutions can reduce their environmental impact and promote a more sustainable future. The analytical study and article content analysis are used to evaluate. Content analysis is used to analyze the findings and reveal the significance of the knowledge creation influences on the knowledge awareness attribute. By examining the interconnectedness of knowledge creation andawareness within the campus management framework, this research seeks to provide insights that can inform strategies for enhancing sustainable practices and promoting a culture of environmental responsibility within academic institutions